If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (-240) = 300 x + -240 = 300 Reorder the terms: -240 + x = 300 Solving -240 + x = 300 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '240' to each side of the equation. -240 + 240 + x = 300 + 240 Combine like terms: -240 + 240 = 0 0 + x = 300 + 240 x = 300 + 240 Combine like terms: 300 + 240 = 540 x = 540 Simplifying x = 540
| 3(x+4)+6=0 | | X^2=162 | | 4y+2+6y^2+3=0 | | 19-15-3= | | 3x^2-5x-1+4x^2+7x-1= | | 20+16-15= | | 4p+3(p+1)=2(2p-6) | | (21-5)8= | | 2x+18+x=90 | | 2x^4-6x^3+34x^2=0 | | 3(x+4)-10=8 | | 7w+3=52 | | 3T-2=7T | | -9d+5=-13 | | 3(x+4)-18=0 | | 3-2(m+4)=5-6m | | 3x+4-6=12 | | x+x+90=27 | | 4-(x-8)=3+2x | | 2x+11=15-6x | | x+x=27 | | 3x+12-6=12 | | x-30=6-2x | | (x-4)(2x+1)= | | 6x+5-7x+3=5x-6x-4 | | 3x+13=9x-8 | | x+x+27= | | 12=3(x+4)-6 | | 9(2x+6)+17= | | 7x-29=-15 | | (3x^2-5x-1)+(4x^2+7x-1)= | | 3(3x-2)=18+x |